2021
DOI: 10.21037/tcr-21-50
|View full text |Cite
|
Sign up to set email alerts
|

Bruton’s tyrosine kinase inhibitors in primary central nervous system lymphoma—evaluation of anti-tumor efficacy and brain distribution

Abstract: Background: Primary central nervous system lymphoma (PCNSL) is an aggressive lymphoma confined to central nervous system. Current treatments including surgery, chemotherapy and whole-brain radiotherapy often fail to achieve satisfactory effect, especially in elderly. As a regimen in targeted therapy, Bruton's tyrosine kinase (BTK) inhibitor ibrutinib has been tested in several clinical trials against PCNSL, offering hope for patients unfit for chemotherapy. We aim to evaluate and compare the anti-PCNSL ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Although the prognosis of RS remains poor, especially with CNS involvement, 3 ibrutinib has been found to be an effective treatment. 4,5 Furthermore, ibrutinib is effective and safe for the treatment of primary CNS lymphoma [6][7][8] and mantle cell lymphoma with CNS involvement. 9,10 The permeability of ibrutinib across the blood-brain barrier was determined by measuring its concentration in the cerebrospinal fluid (CSF) of patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the prognosis of RS remains poor, especially with CNS involvement, 3 ibrutinib has been found to be an effective treatment. 4,5 Furthermore, ibrutinib is effective and safe for the treatment of primary CNS lymphoma [6][7][8] and mantle cell lymphoma with CNS involvement. 9,10 The permeability of ibrutinib across the blood-brain barrier was determined by measuring its concentration in the cerebrospinal fluid (CSF) of patients.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 The permeability of ibrutinib across the blood-brain barrier was determined by measuring its concentration in the cerebrospinal fluid (CSF) of patients. [6][7][8][9][10] The unbound brain-to-plasma concentration ratio of ibrutinib, a pharmacokinetic parameter, was reported to be 9.8% in rats. 8 A CSF-to-plasma ibrutinib concentration ratio of 1-7% has been reported in patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of AEs were hematological toxicities, which occurred more with combined ibrutinib and chemotherapy [82,84]. Only one non-randomized study has been reported for another BTKi, tirabrutinib in the treatment of refractory/relapsed (R/R) PCNSL (n = 44) [85].…”
Section: Bruton's Tyrosine Kinase Inhibitor (Btki)mentioning
confidence: 99%
“…In vitro and in vivo studies demonstrated that Ibrutinib was more effective than Zanubrutinib and Tirabrutinib for the treatment of PCNSL with an ideal pharmacokinetic property in brain distribution. 96 Ibrutinib monotherapy exhibits impressive clinical activity and safety with the ORR reaching 77% in a phase I clinical trial. 97 Similar positive results were obtained in another phase I trial.…”
Section: The Immune-related Mechanisms Of Btk Inhibition In the Centr...mentioning
confidence: 99%